De novo indol‐3‐ylmethyl glucosinolate biosynthesis, and not long‐distance transport, contributes to defence of Arabidopsis against powdery mildew. (26th April 2020) - Hunziker, Pascal; Ghareeb, Hassan; Wagenknecht, Lena; Crocoll, Christoph; Halkier, Barbara Ann; Lipka, Volker; Schulz, Alexander
Abstract: Powdery mildew is a fungal disease that affects a wide range of plants and reduces crop yield worldwide. As obligate biotrophs, powdery mildew fungi manipulate living host cells to suppress defence responses and to obtain nutrients. Members of the plant order Brassicales produce indole glucosinolates that effectively protect them from attack by non‐adapted fungi. Indol‐3‐ylmethyl glucosinolate is constitutively produced in the phloem and transported to epidermal cells for storage. Upon attack, indol‐3‐ylmethyl glucosinolate is activated by CYP81F2 to provide broad‐spectrum defence against fungi. How de novo biosynthesis and transport contribute to defence of powdery mildew‐attacked epidermal cells is unknown. Bioassays and glucosinolate analysis demonstrate that GTR glucosinolate transporters are not involved in antifungal defence. Using quantitative live‐cell imaging of fluorophore‐tagged markers, we show that accumulation of the glucosinolate biosynthetic enzymes CYP83B1 and SUR1 is induced in epidermal cells attacked by the non‐adapted barley powdery mildew Blumeria graminis f.sp. hordei. By contrast, glucosinolate biosynthesis is attenuated during interaction with the virulent powdery mildew Golovinomyces orontii . Interestingly, SUR1 induction is delayed during the Golovinomyces orontii interaction. We conclude that epidermal de novo synthesis of indol‐3‐ylmethyl glucosinolate contributes to CYP81F2‐mediated broad‐spectrum antifungal resistance and that adapted powdery mildews may target this process. Abstract : Indole glucosinolates are part of the plant immunity against compatible and incompatible powdery mildew fungi in Arabidopsis. Upon attack, not only preformed vasculature‐derived, but also epidermally induced, de novo synthesized indole glucosinolates contribute to the defence.